VERBAL VIOLENCE USING PREDICATIONAL STRATEGY IN COMMENTING NEWS UPDATE ON FACEBOOK - Ahmad Zulfahmi Muwafiq; Sumarlam Sumarlam; Diah Kristina (Universitas Sebelas Maret, 2017)
This article address the issue of verbal violence articulated by Facebook users using predicational strategies as proposed by Wodak when commenting news update posted on Indonesian news portal fans pages under the topic of Paris tragedy. As the realisation of predicational strategy, this article explores the form and the meaning of verbal violence linguistically articulated by the users. The data of verbal violence are taken from user comments in four different news fans pages, namely Detik.com, Kompas.com, Liputan6.com, and Tribunnews.com. Employing predicational strategies, there are several linguistic realisations of verbal violence, such as attributes, redicative verb, object or complement of predicate, predicative noun, and predicative adjective. These also reveal several meaning, such as violent action, violent trait, bad habit, mental deficiency, bad condition, exclusion from a social identity, and inclusion to a social identity.